Effect of Cr2O3-TiO2 addition on the physical properties of zirconia toughened alumina - Manshor, Hanisah; Ramli, Abdul Wahid; Ahmad Azhar, Ahmad Zahirani; Abdullah, Ezzat Chan; Ahmad, Zainal Arifin (Trans Tech Publications, 2016)
Zirconia toughened alumina (ZTA) has good mechanical properties and widely used in cutting insert application. Although the ZTA is well known of its good mechanical properties, its still can be improved in order to produce better properties. It can be done by adding additives as reinforcement such as magnesium oxide (MgO), cerium oxide (CeO2), titania (TiO2) and chromia (Cr2O3). The effects of TiO2-Cr2O3 addition on the physical properties of ZTA were investigated in this study. The composition of TiO2 was varied from 0 wt.% to 3.5 wt.% while Cr2O3 was fixed at 5 wt.%. The starting powder materials were mixed by wet mixing for 30 minutes in acetone. Then the powder mixtures were hydraulically pressed at 260 MPa. The green pellets were sintered at 1600 oC for 1 hour using an electrical furnace in presureless condition. The results were characterized by XRD, density, and also Vickers hardness. The ZTA-Cr2O3-TiO2 ceramic composite achieved the highest density of 4.1 g/cm3 and Vickers hardness of 1919 HV prior to the addition of 2.0 wt.% TiO2. Therefore, it can be decisively concluded that the addition of Cr2O3-TiO2 does affected the properties of ZTA.